Equity and other effects of a program facilitating and promoting active travel. (July 2022) - Keall, Michael; Randal, Edward; Abrahamse, Wokje; Chapman, Ralph; Shaw, Caroline; Witten, Karen; Woodward, Alistair; Howden-Chapman, Philippa
Abstract: The proportion of trips involving walking or cycling (active travel) in New Zealand is diminishing. In two small provincial cities, funding was provided to install walking and cycling infrastructure and run programs to promote and normalise active travel. We aimed to analyse effects five years after baseline along with changes in active travel for Māori and people on lower incomes. A total of 2, 500 people were interviewed in person before the start of the intervention and four times subsequently. Some were part of a cohort that was surveyed more than once. Two matched control cities that did not receive the funding provided a comparison group. The program was associated with sustained increases in active travel rates in the intervention cities compared to the controls. Māori increased active travel rates considerably more than non-Māori, as did members of households with below median income. The program was successful in addressing some inequities within a car-dominated transport system.